E-006 Brainstem Reperfusion Injury Following Endovascular Treatment of Posterior Circulation Ischemia. (29th July 2016) - Higashimori, T; Kim, J; Sandhu, D; Streib, C; Tummala, R
Abstract : Introduction: Reperfusion injury is a recognized but fairly uncommon consequence of revascularization of anterior circulation large vessel occlusion. It has not been described in the posterior circulation, perhaps because of the lower incidence of posterior circulation occlusive disease and because many of these lesions were not historically amenable to revascularization. We describe two cases of brainstem hemorrhage following revascularization of vertebrobasilar arterial occlusion. Methods: The medical records and images of patients who underwent revascularization of the posterior circulation were reviewed. Cases were identified from our institutional neuroendovascular database. Results: Two patients with brainstem hemorrhages following angioplasty and stent placement in the posterior circulation were identified. The first patient was a 68 year-old woman with systemic lupus erythematosus and multiple, recurrent posterior circulation strokes. She had bilateral vertebral artery occlusion with poor angiographic collaterals. She underwent uneventful placement of a balloon mounted stent in the left vertebral artery, and a good angiographic result was obtained. Thirty minutes later, she became comatose and a massive pontine hemorrhage was discovered. The second patient was a 78 year-old woman with recurrent syncope and scattered cerebellar strokes. She had flow limiting basilar artery stenosis and required systolic blood pressures >180 mm Hg to maintain consciousness. She could not be maintained without vasopressors and endovascular treatment was performed. She underwent successful angioplasty and stent placement. She was in good neurological condition initially, but 12 hours later she became comatose with a large pontine and midbrain hemorrhage. Both patients expired. Conclusion: Because all other causes seemed implausible, we concluded that both patients died of brainstem reperfusion injury. Because of the improved ability to treat vertebrobasilar occlusive disease, reperfusion injury in the posterior circulation may be increasingly recognized and characterized. Disclosures: T. Higashimori: None. J. Kim: None. D. Sandhu: None. C. Streib: None. R. Tummala: None.